PENERAPAN TIME-DRIVEN ACTIVITY-BASED COSTING PADA PERHITUNGAN HARGA POKOK PRODUK USAHA JASA UNIXON - Astrid Anastasya Jovanka; L Jade Faliany (Universitas Katolik Indonesia Atma Jaya, 2017)
The purpose of this paper is to calculate branding consultant cost using Time-Driven Activity-Based Costing (TDABC). TDABC calculate cost based on activity that is controlled by time. The method that is used in this research is a case study in Unixon, a small business that works in the field of branding, using data from 2016. Interviews were conducted. The cost and activity database was analyzed. The results of this research show that TDABC can be applied in this Company because it qualified the requirements; diversity in product and different time consumption ratio for each product. TDABC provided more accurate cost information by calculating all costs; cost to make and cost to sell. Implementation of TDABC also show time capacity utilization by comparing actual labor hours and work hours that is controlled by government regulation. By understanding this condition, the owner is able to evaluate the amount of job that is done, time consumption, and employee who is involved. To implement TDABC, the Company must consider each steps needed from identifying activity, assign cost to activity, calculate tariff per activity, to calculate cost of product.